2010
DOI: 10.1007/s12155-009-9067-5
|View full text |Cite
|
Sign up to set email alerts
|

Improving Enzymes for Biomass Conversion: A Basic Research Perspective

Abstract: The cost of enzymes for converting plant biomass materials to fermentable sugars is a major impediment to the development of a practical lignocellulosic ethanol industry. Research on enzyme optimization with the goal of reducing the cost of converting biomass materials such as corn stover into glucose, xylose, and other sugars is being actively pursued in private industry, academia, and government laboratories. Under the auspices of the Department of Energy Great Lakes Bioenergy Research Center, we are taking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
146
0
8

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(155 citation statements)
references
References 57 publications
(72 reference statements)
1
146
0
8
Order By: Relevance
“…The main disadvantage of acid hydrolysis is the generation of fermentation inhibitors (Galbe and Zacchi, 2002). The use of microbial enzymes is an attractive alternative for cellulose depolymerization due to the specificity and efficiency of the enzymes as well as the non-inhibitor feature and rapid hydrolysis (Arantes and Saddler, 2010;Banerjee et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The main disadvantage of acid hydrolysis is the generation of fermentation inhibitors (Galbe and Zacchi, 2002). The use of microbial enzymes is an attractive alternative for cellulose depolymerization due to the specificity and efficiency of the enzymes as well as the non-inhibitor feature and rapid hydrolysis (Arantes and Saddler, 2010;Banerjee et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…T. harzianum are frequently reported as control agent against fungal pathogens (Arantes and Saddler 2010;Banerjee et al 2010). However, recent studies have also revealed the potential of this fungus for cellulase production and industrial applications (Ahmed et al 2009;Castro et al 2010aCastro et al , 2010b.…”
Section: Discussionmentioning
confidence: 99%
“…Presently, commercial production of cellulases and xylanases is mostly from fungi such as Trichoderma and Aspergillus species, which may have attained maximal yield, having undergone extensive strain improvement over the years (Banerjee et al, 2010;Peterson and Nevalainen, 2012). Moreover, these commercial enzymes are still limited by the high cost of production, narrow substrate reaction and instability under industrial process dynamics (Motta et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, considerable efforts are being made to increase microbial cellulase and xylanase production by environmental strains (Kim et al, 2007). In that context hemi (cellulolytic) bacterial strains are continuously being sourced from diverse environments with a view to finding better alternative producers or other cellulases and xylanases capable of enhancing existing commercial enzyme cocktail preparations (Banerjee et al, 2010). Therefore investigation on novel bacterial strains adaptable to industrial process dynamics and capable of producing cellulases and xylanases with favourable industrial characteristics is ongoing (Sepahy et al, 2011;de Souza Vandenberghe et al, 2016).…”
Section: Introductionmentioning
confidence: 99%